2017
DOI: 10.1159/000477303
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane Formation Assay to Identify High On-Treatment Platelet Reactivity to Aspirin

Abstract: Platelet inhibition by aspirin is indispensable in the secondary prevention of cardiovascular events. Nevertheless, impaired aspirin antiplatelet effects (high on-treatment platelet reactivity [HTPR]) are frequent. This is associated with an enhanced risk of cardiovascular events. The current gold standard to evaluate platelet hyper-reactivity despite aspirin intake is the light-transmittance aggregometry (LTA). However, pharmacologically, the most specific test is the measurement of arachidonic acid (AA)-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These fixed time points increase the comparability of every regimen. Furthermore, although not all parameters of platelet function tests showed statistically significant results-as the thromboxane production is the primary target of aspirin-sTxB 2 levels can be seen as the most specific test for aspirin effectivity [31]. An important limitation, however, lies in the technical properties of the Platelet Function Analyser (PFA).…”
Section: Discussionmentioning
confidence: 99%
“…These fixed time points increase the comparability of every regimen. Furthermore, although not all parameters of platelet function tests showed statistically significant results-as the thromboxane production is the primary target of aspirin-sTxB 2 levels can be seen as the most specific test for aspirin effectivity [31]. An important limitation, however, lies in the technical properties of the Platelet Function Analyser (PFA).…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of BG in stroke patients will increase the anaerobic glycolysis of ischemic stroke, aggravate the accumulation of lactic acid, and eventually lead to stroke metabolic disorders (12,13). Kong et al (14) reported that TXB 2 is expressed at a low level in blood in a normal state, but when platelets are activated, a large amount of TXB 2 is released into blood, which has the effect of promoting platelet aggregation and vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the AR standard most commonly used and accepted by researchers is that the average aggregation of 10 μmol/L adenosine diphosphate (ADP) is greater than 70%, and the average aggregation of 0.5 mg/ml AA is greater than 20% as proposed by Gum et al (2001). Mohring et al (2017) detected the formation of thromboxane induced by AA through enzyme-linked immunosorbent assay (ELISA) and the AA-induced antiplatelet effect of aspirin by the LTA method. The results showed that there was a non-linear correlation between the formation of thromboxane and the maximum value of AA-induced LTA aggregation (Spearman's rho R 0.7396; 95% CI 0.7208-0.7573, p < 0.0001).…”
Section: Detection and Significance Of Armentioning
confidence: 99%